Hybrid thermosets from vinyl ester resin and acrylated epoxidized soybean oil (AESO) (eXPRESS Polymer Letters)
A series of hybrids composed of styrene crosslinkable vinyl ester (VE) and acrylated epoxidized soybean oil (AESO) were produced via free radical-induced crosslinking. The VE/AESO ratio was changed between 75/25 and 25/75 wt%. Moreover, to support phase grafting the VE/AESO = 50/50 wt% hybrid was modified with phthalic anhydride in various amounts (1, 5 and 10 wt%). The structure of the hybrid systems was investigated by dynamic mechanical thermal analysis (DMTA), differential scanning calorimetry (DSC), and atomic force microscopy (AFM). The properties of the systems were assessed by static flexural and fracture mechanical tests. The resistance to thermal degradation was inspected by thermogravimetric analysis (TGA). The results suggested that the hybrids have an interpenetrating network (IPN) structure. With increasing AESO content the stiffness (modulus), strength and glass transition temperature (Tg) of the hybrids decreased, whereas their ductility increased. Phthalic anhydride caused an adverse trend. Both the fracture toughness and fracture energy increased with increasing AESO content. They were less affected by adding phthalic anhydride phase couplant. Interestingly, the hybrids outperformed the parent VE and AESO in respect to resistance to thermal degradation.